ASP.NET AJAX Programmer's Reference: with ASP.NET 2.0 or ASP.NET 3.5 - Khosravi Shahram (Wiley, 2007)
* Ajax is one of the hottest changes in Web development methods in years; Microsoft's ASP.NET 2.0 AJAX (formerly known as "Atlas") provides Ajax add-ins for ASP.NET developers, and this comprehensive Wrox reference offers coverage of all the ASP.NET 2.0 AJAX pieces